(untitled) (Revista Direito em Debate, 2022)
The aim of this article is the study of informative self-determination and its material recognition as a right of the personality analyzed under the principle of security. The current technological development brings benefits to the community, however, it is observed that the individual has become the product of the Information Society, and this violates the principle of the free development of the personality of the natural person, which justifies the present investigation. The method used is the hypothetical-deductive, and the tested hypothesis is whether the right to informative self-determination is sufficient to guarantee the free development of the personality in a context of a society instrumented by data; the methodology focuses on the bibliographic review of doctrine, legislation, scientific articles, consultation with official agency websites and news published in the media. The results achieved show that informative self-determination is a right that requires concrete elements to support it. The conclusion identifies that the principle of security is one of these bastions to the point of becoming the sine qua non condition for the realization of the right to informative self-determination. The article presents suggestions for strengthening this support network.